2009
DOI: 10.1159/000236904
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Volume and Quality of Laparoscopic Gastrectomy in Japan

Abstract: Background: Laparoscopic gastrectomy (LG) has become the prevailing surgery of choice for gastric cancer, but the impact of hospital volume or operating room (OR) time has not been evaluated. An observational study was conducted to assess the quality of LG based on hospital volume and OR time. Methods: 3,054 LG patients were enrolled in 420 hospitals throughout Japan. Analyzed variables included patient demographics, complications, use of stapling devices or chemotherapy, hospital volume, and teaching status. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Sixteen relevant articles were retrieved from the Medline search: eight for GC (Peeters & van de Velde 2003;Meyer 2005;van Krieken & Nagtegaal 2005;Helyer et al 2007;Kuwabara et al 2009;Qureshi et al 2009;Verlato et al 2009;Jensen et al 2010) and eight for OC (Tanisada et al 2002;Lerut et al 2005;Teshima & Japanes 2005;Gouma & Busch 2007;Wouters et al 2008;Coe et al 2009;Wouters et al 2009;Courrech Staal et al 2010), which were evaluated based on their full text. Globally, 28 QIs were retrieved from these published sources.…”
Section: Construction Of Qi Setsmentioning
confidence: 99%
“…Sixteen relevant articles were retrieved from the Medline search: eight for GC (Peeters & van de Velde 2003;Meyer 2005;van Krieken & Nagtegaal 2005;Helyer et al 2007;Kuwabara et al 2009;Qureshi et al 2009;Verlato et al 2009;Jensen et al 2010) and eight for OC (Tanisada et al 2002;Lerut et al 2005;Teshima & Japanes 2005;Gouma & Busch 2007;Wouters et al 2008;Coe et al 2009;Wouters et al 2009;Courrech Staal et al 2010), which were evaluated based on their full text. Globally, 28 QIs were retrieved from these published sources.…”
Section: Construction Of Qi Setsmentioning
confidence: 99%
“…In the majority of these studies, the effect of hospital volume on postoperative mortality was investigated, with variable results. 12,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Of note, in most large studies, a benefit for high annual hospital volume was found, whereas in smaller studies no difference between high-volume and low-volume hospitals was detected (Fig. 2).…”
Section: Structure Indicatorsmentioning
confidence: 99%
“…To the best of our knowledge, most studies showed no relationship between hospital volume and postoperative morbidity 18, 20, 21, 26, 27, 28. Morbidity rate is generally affected by patient characteristics such as comorbidities, acuity of presentation, and age 29.…”
Section: Resultsmentioning
confidence: 96%